Exploring Teachers and Students’ Perspectives on the Role of Debates in Enhancing EFL Students Speaking Skill The Case of Second Year LMD Students at the University of Souk-Ahras - BOUARGOUB Soundes (My University, 2023)
Abstract This research delves into the exploration of students' and teachers' viewpoints concerning the efficacy of debates in augmenting English as a Foreign Language (EFL) students' speaking skills. The study specifically centers around the University of Mohammed Cherif Messaadia in Souk Ahras, where it engaged 57 students and conducted in-depth interviews with four teachers. The overarching objective was to examine whether debates contribute positively to enhancing EFL students' speaking proficiency. The research data were collected through a combination of quantitative and qualitative methods. A questionnaire was administered to the sampled 57 students to gauge their perspectives on the role of debates in refining speaking skills. Moreover, the qualitative dimension involved conducting interviews with four teachers, which provided nuanced insights into their perceptions of debate as a pedagogical tool. The findings of the study reveal a confirmed alignment with the hypothesis, affirming the significance of debates in fostering EFL students' speaking proficiency. Both students and teachers exhibited favorable attitudes towards the use of debates for this purpose. These outcomes underscore the importance of incorporating debate activities into EFL classrooms to cultivate effective oral communication skills among students. The implications of this research contribute to the pedagogical discourse surrounding language instruction methodologies, offering educators and curriculum designers valuable insights into enhancing EFL speaking skills through the integration of debates ------------------------ الملخص هذا البحث يبحث في وجهات نظر الطلاب والمعلمين حول فعالية المناقشات في تعزيز مهارات التحدث لدى طلاب اللغة الإنجليزية كلغة أجنبية. يركز البحث على وجه التحديد على جامعة محمد الشريف مساعدية في سوق أهراس ، حيث شارك 57 طالبًا وأجريت مقابلات عميقة مع أربعة معلمين. الهدف العام هو فحص ما إذا كانت المناقشات تساهم بشكل إيجابي في تعزيز كفاءة التحدث لدى الطلاب. جمعت بيانات البحث من خلال الجمع بين الأساليب الكمية والنوعية. تم إرسال استبيان إلى 57 طالبًا تم اختيارهم عشوائيًا لقياس وجهات نظرهم حول دور المناقشات في صقل مهارات التحدث. بالإضافة إلى ذلك، تضمنت البعد النوعي إجراء مقابلات مع أربعة معلمين ، مما وفر رؤى دقيقة حول تصوراتهم للمناقشات كأداة تربوية. نتائج الدراسة تؤكد صحة الفرضية، وتؤكد أهمية المناقشات في تنمية كفاءة التحدث لدى الطلاب. أظهر كل من الطلاب والمعلمين مواقف إيجابية تجاه استخدام المناقشات لهذا الغرض. تؤكد هذه النتائج أهمية إدراج أنشطة المناقشة في الفصول الدراسية لتنمية مهارات الاتصال الشفوي الفعالة بين الطلاب. تساهم نتائج هذا البحث في الخطاب التربوي المحيط بطرق تدريس اللغة، وتقدم للمعلمين ومصممي المناهج الدراسية رؤى قيمة لتعزيز مهارات التحدث لدى الطلاب من خلال دمج المناقشات ------------------ Résumé Cette recherche étudie les points de vue des étudiants et des enseignants sur l'efficacité des discussions pour améliorer les compétences orales des étudiants en langue. L'anglais comme langue étrangère. La recherche porte spécifiquement sur l'Université Mohamed Cherif Messaadia de Souk Ahras, où il a participé 57 étudiants et des entretiens approfondis ont été menés avec quatre enseignants. L'objectif global est d'examiner si les discussions contribuent positivement à Améliorer la maîtrise de l’expression orale des étudiants. Les données de recherche ont été collectées en combinant des méthodes quantitatives et qualitatives. Un questionnaire a été envoyé À 57 étudiants sélectionnés au hasard pour mesurer leur point de vue sur le rôle des discussions dans le perfectionnement des compétences orales. En plus de La dimension qualitative comprenait donc des entretiens avec quatre enseignants, qui ont permis d'obtenir un aperçu précis de leur perception des discussions en tant qu'outil. Éducatif. Les résultats de l’étude confirment la validité de l’hypothèse et confirment l’importance des discussions dans le développement de la compétence orale des élèves. Montrer à tout le monde Les étudiants et les enseignants ont une attitude positive à l’égard de l’utilisation des discussions à cette fin. Ces résultats soulignent l’importance d’inclure des activités de discussion dans Salles de classe pour développer des compétences de communication orale efficaces entre les étudiants. Les résultats de cette recherche contribuent au discours pédagogique En ce qui concerne les méthodes d'enseignement des langues, il offre aux enseignants et aux concepteurs de programmes des informations précieuses sur l'amélioration des compétences orales des élèves En intégrant des discussions
Keywords: speaking skill; debate technique; مهارة الكلام، تقنية النقاش; expression orale; technique de discussion